The Protection of National Minorities within the Council of Europe: An Analytical Review - Aslan, Jabbar; Aslani, Khabbat (Kathmandu School of Law Review, 2013)
According to the preamble of the Framework Convention for the Protection of National Minorities, which has entered into force on 1 February 1998, minority rights are an integral part of fundamental human rights. This instrument is the ever legally binding treaty in the regional and also universal level that taken on great importance in addressing the challenges of minority protection in evolving and increasingly diverse societies. So, this paper has an analytical approach to the protection of minorities within the Council of Europe and for this, especially, focuses on the Framework Convention: namely its content, its rights-holders, and also- the most important point of view - the problems, challenges and tasks that this legally instrument faces with it in practice. One must take into account that the Framework Convention has passed 13 years of its birth and the authors aim to analyse its achievements and in the same time, its challenges as well. Thus, we reiterate once more that our method is analytical to examine the topic.